Does Fundus Fluorescein Angiography Procedure Affect Ocular Pulse Amplitude? - Gökhan Pekel; Semra Acer; Ramazan Yagci; Ebru Nevin Cetin; Mehmet Can Hiraali; Hüseyin Kaya (Journal of Ophthalmology)
Purpose. This study examines the effects of fundus fluorescein angiography (FFA) procedure on ocular pulse amplitude (OPA) and intraocular pressure (IOP). Materials and Methods. Sixty eyes of 30 nonproliferative diabetic retinopathy patients (15 males, 15 females) were included in this cross-sectional case series. IOP and OPA were measured with the Pascal dynamic contour tonometer before and after 5 minutes of intravenous fluorescein dye injection. Results. Pre-FFA mean OPA value was  mmHg and post-FFA mean OPA value was  mmHg (). Pre-FFA mean IOP value was  mmHg and post-FFA mean IOP value was  mmHg (). Conclusion. Although both mean OPA and IOP values were decreased after FFA procedure, the difference was not statistically significant. This clinical trial is registered with Australian New Zealand Clinical Trials Registry number ACTRN12613000433707.